Budhigandaki Hydroelectric Project is Unlikely to be Implemented as Recommended by Tractebel Engineering - Shrestha, Hari Man (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Tractebel Engineering SA France has recommended 263 m high double curvature arch dam for the Budhigandaki Hydroelectric Project for generation of 1200 MW. The author, based on findings of the Tractebel’s feasibility study itself, gives reasons why the project is unlikely to be implemented as recommended by the consultant. Further, the author raises the question with the government why this project was declared as one of the projects of national pride and was ready for committing to funding beforehand for the preparation of detail design, tender documents and tender drawings in a single package contract along with the feasibility study when the investment decision could only be taken after ascertaining the soundness/ attractiveness of the project on technical, economical, financial and socio-environmental grounds through feasibility and Environmental Impact Assessment (EIA) studies. The author also believes that the project could become more attractive if the downstream benefits from flow regulation in existing irrigation project in India could be accounted for and two potential hydroelectric projects in Nepal at the downstream reaches could be implemented first to derive additional power benefits in these two projects from flow regulation. HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 17, July 2015